Pea Aphids (Hemiptera: Aphididae) Have Diurnal Rhythms When Raised Independently of a Host Plant. Issue 1 (23rd March 2016) - Joschinski, Jens; Beer, Katharina; Helfrich-Förster, Charlotte; Krauss, Jochen
Abstract: Seasonal timing is assumed to involve the circadian clock, an endogenous mechanism to track time and measure day length. Some debate persists, however, and aphids were among the first organisms for which circadian clock involvement was questioned. Inferences about links to phenology are problematic, as the clock itself is little investigated in aphids. For instance, it is unknown whether aphids possess diurnal rhythms at all. Possibly, the close interaction with host plants prevents independent measurements of rhythmicity. We reared the pea aphid Acyrthosiphon pisum (Harris) on an artificial diet, and recorded survival, moulting, and honeydew excretion. Despite their plant-dependent life style, aphids were independently rhythmic under light–dark conditions. This first demonstration of diurnal aphid rhythms shows that aphids do not simply track the host plant's rhythmicity.